Analysis of Live Streaming, Bundling, and Customer Engagement on Purchasing Decisions at PT Astra TSO Auto2000 Binjai - Rizky Amanda; Megasari Gusandra; Ocdy Amalia (Journal of Management, Economic, and Accounting, 2026)
The goal of this study was to look into how live streaming, bundling, and consumer contact influenced the purchasing decisions of PT Astra TSO Auto2000 Binjai clients. The study employed a quantitative associative technique. The Slovin algorithm and a simple random selection procedure were used to choose a sample of 90 respondents from the 916 participants in the study. The primary data gathered through the distribution of questionnaires was processed using SPSS software version 24. Multiple linear regression was employed in the data analysis to investigate the relationships between the independent and dependent variables. The results showed that live streaming, bundling, and consumer interaction had a good and significant impact on purchase decisions, both partially and concurrently. The regression result for live streaming was 0.283, with a significance level of 0.003 and a t-value of 3.107. Bundling had a significance level of 0.001, a regression coefficient of 0.275, and a t-value of 3.535. The regression value for customer involvement was 0.303, with a significance level of 0.000 and a t-value of 4.456. The significance level was 0.000, and the F-value was 106.340. According to the highest regression value, customer participation was identified as the most important element influencing purchase decisions. According to the coefficient of determination (modified R2) of 0.780, the three independent variables may explain 78.0% of the variation in purchase decisions. Furthermore, a correlation coefficient (R) of 0.888 suggested a highly significant relationship between the independent and dependent variables.